Penyuluhan Kesehatan tentang Faktor Penyebab Kekambuhan Pasien Skizofrenia - Dwi Kartika Pebrianti (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2021)
Schizophrenia is a disease that affects the brain and causes strange and disturbed thoughts, perceptions, emotions, movements and behaviors called schizophrenia (Videbeck, 2008). Globally, the recurrence rate in people with mental disorders reaches 50% -92% due to non-compliance in treatment or due to lack of support and vulnerable living conditions with increased stress (Sheewangisaw, 2012). Clients diagnosed with schizophrenia are estimated to have a 50% relapse in the first year, 70% in the second year after discharge from hospital, and a 100% recurrence in the fifth year. . Data on patient visits at the Outpatient Polyclinic of RSJD Jambi Province in 2016 amounted to 38,330 visits, of which 35,448 visits were repeat visits and the remaining 2882 were new visits. It is hoped that the results of health education activities for patients and their families will understand the concept of nursing problems that cause mental disorder patients to recur.